Quantitative evaluation of the efficacy of non-replicating vaccines for controlling African swine fever in domestic pigs: a systematic review and meta-analysis - Ntakiyisumba, Eurade; Tanveer, Maryum; Hirwa, Fabrice; Won, Gayeon (Frontiers in Veterinary Science, 2025)
BackgroundThe African swine fever virus (ASFV), prevalent globally, causes high mortality and morbidity in domestic pigs. However, there is a lack of effective treatment or vaccines against ASFV infection despite the ongoing research in this field.MethodsIn this systematic review and meta-analysis, we conducted a quantitative evaluation of the efficacy of non-replicating vaccines against ASFV. The vaccine efficacy (VE) was analyzed based on three key disease outcomes: mortality, fever, and clinical symptoms after infection.ResultsThe search of relevant electronic databases yielded 23 studies for inclusion in the review. Vaccination with subunit vaccines significantly reduced mortality risk in vaccinated pigs compared to that in controls (p = 0.02), with a relative risk (RR) of 0.90 (95% CI: 0.83–0.98), indicating a VE of 10% (95% CI: 2–17). However, subunit vaccines did not substantially reduce the risk of fever and other clinical symptoms in vaccinated pigs, with a RR of 0.97 (95% CI: 0.93–1.01) for both outcomes. Moreover, inactivated vaccines did not provide any protection against mortality (RR = 1.01, 95% CI: 0.95–1.06) or other clinical signs (RR = 1.00, 95% CI: 1.00–1.00). No significant between-study heterogeneity was detected, indicating consistent findings across different vaccination trials. Thus, currently available non-replicating vaccines fail to deliver the protection required for field applications.ConclusionCurrently, subunit vaccines are more likely to serve as long-term options for vaccine development strategies. Further research is essential to deepen our understanding of the roles and significance of humoral and cellular immune responses against ASFV, and to identify critical viral antigens that can induce effective protective immunity.